Effects of Environmental Factors on the Abundance, Biomass, and Individual Weight of Juvenile Red King Crabs in the Barents Sea - Dvoretsky, Alexander G.; Dvoretsky, Vladimir G. (Frontiers in Marine Science, 2020)
We examined the effeсts of environmentаl fаctоrs (water temperature, the North Atlantic Oscillation winter index – NAOw, and cod biomass) on the abundance (population number), biomass and mean individual weight of juvenile red king crab (Paralithodes camtschaticus) at a typical coastal site of the Barents Sea, Dalnezelenetskaya Bay, a place of red king crab introduction. Current-year abundance and stock data for 3–5-year-old crabs were positively related to water temperature in September and October. The biomass of crabs at age 0–2 yr was positively correlated with lag 1 water temperature in August, while the abundance of age 0–5 yr was positively correlated to the NAOw indicating more favorable habitat conditions in warmer periods. The abundance of crabs at age 3–5 yr was negatively correlated to December temperature and mean water temperature and temperature anomaly with a 1-year lag. These temperature relationships, together with negative correlations between stock indices of crabs and cod (Gadus morhua) and positive relationships between mean crab weight and cod biomass, suggests that the fish predation, which is higher in warmer years, has a more important role in mortality of 3–5 yr crabs than 0–2 yr crabs. Our findings may be useful for modeling recruitment processes and management of red king crab in the Barents Sea.